Estos documentos pueden consultarse en el CID-Palmero - Comunicaciones, Departamento (Boletín El Palmicultor, 2018)
Achieving sustainable cultivation of oil palm : introduction, breeding and cultivation techniques Palmas en Venezuela : autóctononas y exóticas - Venezuela